2017
DOI: 10.1002/jcb.26041
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B Protects Against Pressure Overload Induced Cardiac Hypertrophy

Abstract: Lack of effective anti-cardiac hypertrophy drugs creates a major cause for the increasing prevalence of heart failure. In the present study, we determined the anti-hypertrophy and anti-fibrosis potential of a natural plant triterpenoid, Cucurbitacin B both in vitro and in vivo. Aortic banding (AB) was performed to induce cardiac hypertrophy. After 1 week of surgery, mice were receive cucurbitacin B treatment (Gavage, 0.2 mg/kg body weight/2 day). After 4 weeks of AB, cucurbitacin B demonstrated a strong anti-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The decreased autophagy usually results in the aggregation of abnormal proteins, thereby inducing dysfunction of cytoskeleton proteins and decrease in cellular functions, which finally contributes to cell death [24]. Xiao Y et al reported that cucurbitacin-b can ameliorate the hypertrophy and myocardial fibrosis in pressure-overload mouse cells [25]. Liu S et al also suggested that activated autophagy can improve the myocardial fibrosis induced by angiotensin II [26].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased autophagy usually results in the aggregation of abnormal proteins, thereby inducing dysfunction of cytoskeleton proteins and decrease in cellular functions, which finally contributes to cell death [24]. Xiao Y et al reported that cucurbitacin-b can ameliorate the hypertrophy and myocardial fibrosis in pressure-overload mouse cells [25]. Liu S et al also suggested that activated autophagy can improve the myocardial fibrosis induced by angiotensin II [26].…”
Section: Discussionmentioning
confidence: 99%
“…The cucurbitacin B mediated that significantly mitigated cardiac hypertrophy could be attributable to the autophagy increase. It was related to the blockade of Akt/mTOR/FoxO3a pathway [ 24 ]. In addition, MF is a prominent pathological characteristic in diabetic myocardial damage [ 32 ].…”
Section: Potential Effect Of Autophagy In the Treatment Of Myocardmentioning
confidence: 99%
“…This condition is also associated with enhanced protein synthesis and activation of foetal cardiac gene expression . Without effective intervention, cardiac hypertrophy is not effectively intervened, eventually develops into HF eventually develops . Undoubtedly, cardiac hypertrophy plays an important role in the occurrence and development of HF.…”
Section: Introductionmentioning
confidence: 99%